2010
DOI: 10.1137/080733036
|View full text |Cite
|
Sign up to set email alerts
|

Application of Standard and Refined Heat Balance Integral Methods to One-Dimensional Stefan Problems

Abstract: Abstract. The work in this paper concerns the study of conventional and refined heat balance integral methods for a number of phase change problems. These include standard test problems, both with one and two phase changes, which have exact solutions to enable us to test the accuracy of the approximate solutions. We also consider situations where no analytical solution is available and compare these to numerical solutions. It is popular to use a quadratic profile as an approximation of the temperature, but we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
102
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 106 publications
(103 citation statements)
references
References 42 publications
(137 reference statements)
0
102
0
1
Order By: Relevance
“…The Heat Balance Integral Method (HBIM) was developed by Goodman, see [7,12], to find approximate solutions to the heat equation and Stefan problems. In fact it is an adaptation of the earlier method of von Kárman and Pohlhausen for analysing boundary layer flow [24].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Heat Balance Integral Method (HBIM) was developed by Goodman, see [7,12], to find approximate solutions to the heat equation and Stefan problems. In fact it is an adaptation of the earlier method of von Kárman and Pohlhausen for analysing boundary layer flow [24].…”
Section: Introductionmentioning
confidence: 99%
“…Wood [26] showed that even for the quadratic there are six distinct formulations and the one employed by Goodman is generally only the third most accurate. In fact there is a seventh formulation, see [12]. Antic & Hill [2] employ a cubic profile in the study of diffusion in grain silos.…”
Section: Introductionmentioning
confidence: 99%
“…In the original HBIM the value n = 2 was employed, although other values have been used in later studies (often motivated by numerical solutions), see [19]. For now we leave it unspecified.…”
Section: Solution With the Hbimmentioning
confidence: 99%
“…The popularity of the HBIM is mainly due to its simplicity. However, in its original form there are a number of drawbacks, primarily a lack of accuracy for certain problems but also the rather arbitrary choice of approximating function, see [19] for a more detailed description of the method and problems. Recently a number of variants of the HBIM have been developed which address the issues and have led to simple solution methods that, over physically realistic parameter ranges, have proved more accurate than second order perturbation solutions [20,21,22,23].…”
Section: Solution With the Hbimmentioning
confidence: 99%
See 1 more Smart Citation